Working alliance and its link to guidance in an internet-based intervention for depressive disorders: a secondary analysis of a randomized controlled trial - Haaf, Raoul; Schefft, Cora; Krämer, Rico; Klein, Jan Philipp; Köhler, Stephan (Frontiers in Psychiatry, 2024)
Background Guided Internet-based interventions (IBIs) are typically found to be more effective than unguided ones, but the reasons behind this are not well understood. The therapist-client working alliance, crucial in face-to-face psychotherapy, is also increasingly recognized as an important factor in IBIs. This study examines trajectories of the working alliance and its relationship to therapeutic guidance through a secondary analysis of a randomized controlled trial (RCT) on Selfapy, a 12-week IBI based on cognitive behavioral therapy for depressive disorders. The trial compared a therapist-guided version (with weekly calls) to an unguided version (n = 301, mean age 37 years, 83% female, mean BDI-II = 30.09). Methods Based on an intention-to-treat approach, this study investigates within- and between-group differences in the quality of the working alliance, assessed with the WAI-SR questionnaire at mid- and post-treatment via repeated measures ANOVA. Furthermore, correlations and mediation analyses were conducted to explore the relationship between the working alliance and outcomes, as well as adherence parameters. Results Findings indicate that the IBI was successful in fostering a robust working alliance in both intervention groups, with similar ratings at mid-treatment but significantly higher ratings in the guided group at post-treatment (Cohen’s d = -0.38). Post-treatment working alliance scores were positively linked to symptom reduction at post-treatment (guided: r = .25, unguided r = .15) and follow-up (guided: r = .25, unguided: r = .17). In the unguided group, the association was primarily driven by the subscale task. Serial mediation analysis indicated that the relationship between guidance and outcomes at follow-up was mediated by working alliance (b = 0.59; 95% CI: 0.14, 1.22) and a link between working alliance and adherence (b = 0.15; 95% CI: 0.04, 0.34). Conclusions Considering limitations like using a questionnaire developed for face-to-face therapy, findings support the importance of the working alliance in guided IBIs, while also providing new insights into its role and formation in unguided IBIs. The potential benefits of a strong working alliance, notably by improving adherence, may prove crucial for integrating guided as well as unguided IBIs into routine use, indicating the need for additional research in this context. Clinical Trial Registration https://tinyurl.com/2p9h5hnx, German Clinical Trials Register DRKS00017191.